2021
DOI: 10.1007/s12144-021-01910-5
|View full text |Cite
|
Sign up to set email alerts
|

Contextual effects on smile perception and recognition memory

Abstract: Most past research has focused on the role played by social context information in emotion classification, such as whether a display is perceived as belonging to one emotion category or another. The current study aims to investigate whether the effect of context extends to the interpretation of emotion displays, i.e. smiles that could be judged either as posed or spontaneous readouts of underlying positive emotion. A between-subjects design (N = 93) was used to investigate the perception and recall of posed sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…Also, smiles were misremembered as having more of the physical attributes (i.e., Duchenne marker) associated with spontaneous enjoyment when they appeared in the happy than polite context condition. Together, these findings indicate that social context information is routinely encoded during emotion perception, thereby shaping the interpretation and recognition memory of facial expressions" [43].…”
Section: Arguments For Naturalistic Researchmentioning
confidence: 91%
“…Also, smiles were misremembered as having more of the physical attributes (i.e., Duchenne marker) associated with spontaneous enjoyment when they appeared in the happy than polite context condition. Together, these findings indicate that social context information is routinely encoded during emotion perception, thereby shaping the interpretation and recognition memory of facial expressions" [43].…”
Section: Arguments For Naturalistic Researchmentioning
confidence: 91%
“…Hence, contextual information is likely to influence the interpretation of a smile more than other expressions (Ekman et al, 1982;Wallbott, 1988). Whilst extant research has shown that context does affect smile evaluations, this work has generally focused on ratings of emotion, genuineness, or authenticity (Gagnon et al, 2022;Krumhuber, Hyniewska, et al, 2023;Mui et al, 2020;Namba et al, 2020). For example, Namba et al (2020) found that "happy" visual background contexts and vignettes both led to increased ratings of smile genuineness relative to when the same expressions were presented in isolation, whereas "polite" backgrounds and vignettes reduced genuineness ratings.…”
Section: The Bidirectional Relationship Between Smiles and Situationa...mentioning
confidence: 99%
“…For example, Namba et al (2020) found that "happy" visual background contexts and vignettes both led to increased ratings of smile genuineness relative to when the same expressions were presented in isolation, whereas "polite" backgrounds and vignettes reduced genuineness ratings. Likewise, verbal descriptions of eliciting situations strongly affected evaluations of dynamic (Mui et al, 2020) and static smiles in the sense that smiles viewed in happy contexts were misremembered as having more distinctive cheek raising (Krumhuber, Hyniewska, et al, 2023) traditionally implicated as a marker of smile genuineness (Ekman, 1992;Ekman et al, 1990;Frank & Ekman, 1993). Such effects may be especially amplified when mimicry is blocked (Maringer et al, 2011;Orlowska et al, 2020Orlowska et al, , 2021.…”
Section: The Bidirectional Relationship Between Smiles and Situationa...mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, people assume that DSs uniquely reflect genuine positive affect. They also hold a priori beliefs regarding the likely occurrence of authentic smiles (Maringer et al, 2011), and misremember non-Duchenne smiles (NDSs) as more Duchenne-like in appearance when previously viewed in a genuine happy situation (Krumhuber et al, 2021). Hence, there are culturally shared beliefs about the smile and specifically the DS as indicators of positive affect, but this expressive stereotype is not indicative of the actual co-occurrence between affect and expression.…”
Section: Perception: What Dss Actually Conveymentioning
confidence: 99%